Protocol to develop force-generating human skeletal muscle organoids - Mina Shahriyari; Malte Rinn; Arne D. Hofemeier; Artem Babych; Wolfram-Hubertus Zimmermann; Malte Tiburcy (STAR Protocols, 2024)
Summary: Force generation is an essential property of skeletal muscle models in vitro. We describe a versatile 1-step procedure to direct undifferentiated human pluripotent stem cells (PSCs) into contractile skeletal muscle organoids (SMOs). Our protocol provides detailed steps for 3D casting of PSCs using either collagen-I/Matrigel- or fibrin/Geltrex-based hydrogels, SMO differentiation, and application of different culture platforms for mechanical loading and contractility analysis. The SMO model may be particularly useful to study human muscle development and developmental skeletal muscle disorders in vitro.For complete details on the use and execution of this protocol, please refer to Shahriyari et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.